The Influence of Medical Service Quality and Price on Patient Satisfaction and Its Impact on Patient Loyalty (Study on Patients of Pro Medika Laboratory, Bandung City) - Dwi Suntariyani; Agus Mulyana; Suryaman Suryaman (Greenation Publisher & Yayasan Global Research National, 2023)
The purpose of this study was to obtain an overview of service quality, Value, Patient Satisfaction, and Patient Loyalty at the Pro Medika Laboratory in Bandung City; and to determine the direct and indirect influence of Service Quality and Price on Patient Satisfaction and Patient Loyalty; and to analyze the influence of Patient Satisfaction on Patient Loyalty. The research method used in this study was a descriptive survey and an explanatory survey, the unit of analysis in this study was Patients at the Pro Medika Laboratory in Bandung City with a sample of 30 people. The type of investigation was causality, and the time horizon in this study was cross-sectional. This study concluded that Service Quality, Price, Patient Satisfaction and Patient Loyalty at the Pro Medika Laboratory in Bandung City were in good condition, quite affordable, satisfying and quite loyal. In addition, service quality and price have a positive and significant influence on patient satisfaction and patient loyalty at the Pro Medika Laboratory in Bandung City. Likewise, patient satisfaction has a positive and significant influence on patient loyalty.